Pengaruh Strategi Marketing Mix 4P Terhadap Tingkat Penjualan Kamar di Hotel Grand Keisha By Horison Yogyakarta - Cinditia Pramono; Titik Akiriningsih; Agus Gunawan (Jurnal Pariwisata Indonesia, 2019)
The research objectives are (1) to find out whether the product strategy has an effect on the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. (2) To find out whether the price strategy has an effect on the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. (3) To find out whether the place strategy has an effect on the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. (4) To find out whether the promotion strategy has an effect on the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. The data collection techniques of this study were observation, interviews and documentation. The results of this study can be concluded that (1) the product strategy affects the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. (2) The price strategy affects the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. (3) The place strategy has an effect on the level of room sales at the Grand Keisha Hotel by Horison Yogyakarta. (4) The promotion strategy has an effect on the level of room sales at the Grand Keisha Hotel by Horizon.